Promoting Articular Cartilage Regeneration through Microenvironmental Regulation - Kai Liu; Bingjun Zhang; Xiaoling Zhang (Journal of Immunology Research)
In recent years, as the aging population continues to grow, osteoarthritis (OA) has emerged as a leading cause of disability, with its incidence rising annually. Current treatments of OA include exercise and medications in the early stages and total joint replacement in the late stages. These approaches only relieve pain and reduce inflammation; however, they have significant side effects and high costs. Therefore, there is an urgent need to identify effective treatment methods that can delay the pathological progression of this condition. The changes in the articular cartilage microenvironment, which are complex and diverse, can aggravate the pathological progression into a vicious cycle, inhibiting the repair and regeneration of articular cartilage. Understanding these intricate changes in the microenvironment is crucial for devising effective treatment modalities. By searching relevant research articles and clinical trials in PubMed according to the keywords of articular cartilage, microenvironment, OA, mechanical force, hypoxia, cytokine, and cell senescence. This study first summarizes the factors affecting articular cartilage regeneration, then proposes corresponding treatment strategies, and finally points out the future research direction. We find that regulating the opening of mechanosensitive ion channels, regulating the expression of HIF-1, delivering growth factors, and clearing senescent cells can promote the formation of articular cartilage regeneration microenvironment. This study provides a new idea for the treatment of OA in the future, which can promote the regeneration of articular cartilage through the regulation of the microenvironment so as to achieve the purpose of treating OA.